Knee morphometric risk factors for acute anterior cruciate ligament injury in skeletally immature patients. (April 2015) - Shaw, K. Aaron; Dunoski, Brian; Mardis, Neil; Pacicca, Donna
Study design: Retrospective, case–control. Purpose: Knee morphometric risk factors for noncontact anterior cruciate ligament (ACL) injury have been a popular topic with skeletally mature patients. Little research has focused on the skeletally immature, with conflicting conclusions. This study performs a comprehensive analysis of identified parameters thought to predispose to ACL injury in a skeletally immature cohort. Methods: A retrospective review of pediatric patients undergoing knee magnetic resonance imaging (MRI) was performed over a 4-year period. Inclusionary criteria included mid-substance ACL disruption, skeletal immaturity, noncontact injury, without associated ligamentous disruption, and no medical condition associated with ligamentous laxity. MRI studies were analyzed by a pediatric musculoskeletal radiologist, measuring identified bony parameters, and compared with an age-matched control group without ligamentous injury. Data were analyzed using unpaired t -tests and logistic regression. Results: One hundred and twenty-eight patients sustained an ACL disruption, 39 met all inclusionary criteria (66 excluded for associated ligamentous disruption, 23 skeletally mature, three traumatic mechanisms, one with Marfan syndrome). When compared to an age-matched control cohort, the notch width index (NWI) was found to be significantly smaller in the ACL-injured group ( p = 0.046). Subgroups analysis demonstrated significant differences in morphometric parameters between subjects with isolated ACL injuries and concomitant medial collateral ligament (MCL) strain. Conclusions: The NWI was significantly smaller in the ACL injury group. Significant differences were noted between isolated ACL injuries and ACL injuries with an MCL strain. This study further highlights the need for incorporating associated injury patterns when investigating the influence of morphometric factors for ACL injury in the skeletally immature. Level of evidence: Level III.